Firm-level circular innovations in European transition economies - JORGJI, Etis; GJIKA, Aida; KULE, Ditjona (Edelweiss Applied Science and Technology, 2025)
Circular innovation enables firms to achieve environmentally sustainable growth through new products and processes that maximize resource efficiency and minimize pollution. Several factors influence the decision of firms to innovate and eventually transition to circular models to reduce environmental impacts and generate a sustainable growth model. This study analyzes the drivers of circular innovation using Flash Eurobarometer firm survey data across European Transition Economies. This study employs a binary choice model to examine such drivers, focusing on two types of innovation: the first type is measured as actions of firms in selling residues or waste to other companies, and the second type of innovation is measured as actions of firms in recycling or reusing materials or waste within the company. Our empirical results suggest that larger and older firms, those with high annual turnover, and those with higher investment in resource efficiency are more likely to innovate. Overall, the study outlines the importance of firm characteristics such as size in terms of the number of employees and turnover, age, and sector of operation for circular innovation adoption in transition economies. The findings supplement the understanding of the drivers enabling the transition towards sustainability in emerging regional contexts.